Cloning, expression and purification of Leptospira LigB antigen in Escherichia coli - Lan Anh, Le Thi; Thi Hang, Minh; Thi Thu Hien, Nguyen; Thi Ha Giang, Pham; Phi Long, Trieu; Van Anh, Le Thi; Thi Ha Thanh, Dao; Thi Thu Thuy, Can; Huu Duc, Nguyen (Vietnam Journal of Biotechnology, 2020)
Leptospira is one of the most common zoonotic diseases in the tropics and subtropics. Humans are infected by exposure to Leptospira contained water or food sources. Leptospirosis usually breaks out after the flood and causes several consequences for people and economy. Leptospirosis disease, if not rapidly detected and treated promptly, it causes serious consequences such as acute hepatitis-kidneys, meningitis and bleeding, heart and nerve complications, and severe illness can lead to death. Therefore, quick and accurate detection of Leptospira pathogen plays a very important role in Leptospirosis disease treatment. Among antigens of Leptospira, a conserved domain of LigB antigen (Leptospiral immunoglobulin-like protein) was reported that is present in the most of pathogenic serovars of Leptospira, but not in the non-pathogenic Leptospira biflexa, thus this conserved domain was used for production of Leptospirosis detection kits as well as vaccine for Leptospirosis. In order to create a kit for Leptospirosis diagonostic, especially detect anti-Leptospira antibodies in Leptospira infected serum and plasma samples, about 1kb gene fragment encoding for conserved domain of LigB (about 36 kb in molecular weight) was used as the material for producing of LigB protein by DNA recombinant technology. In this study, we present the results for cloning, expressing a conserved domain of LigB antigen in E. coli cells and purifying protein by affinity chromatography collumn. The result indicates that recombinant LigB protein was successfully expressed in E. coli Rosetta 1 and purified by Hitrap chealating collumn. The LigB protein concentration after purification reached 60 mg/L medium with 98% purity. This purified protein will be used as the materials for creating Leptospirosis kit.